Pancreatic metastases from tumors in the urogenital tract - Strobel, Oliver; Büchler, Markus W. (Gastrointestinal tumors, 2015)
Background: Isolated pancreatic metastases or pancreatic metastases with limited extrapancreatic disease are uncommon and account for only 2-4% of resected malignant pancreatic lesions in surgical series. However, clear-cell renal cell carcinoma is the predominant primary tumor and accounts for more than 60% of cases with isolated pancreatic metastases. Pancreatectomy is the treatment of choice for most patients with isolated pancreatic metastases from renal cell cancer. Summary: This review provides an overview of clinical presentation and diagnosis as well as surgical management, including patient selection for surgery and surgical technique for pancreatic metastases of renal cell carcinoma. Key Message: Although there is no high-level evidence that surgical resection of pancreatic metastases improves survival, the survival results of several observational series and of systematic reviews are promising and support pancreatic resection as part of a multimodal treatment. The reported median survival and 5-year survival rates after pancreatic resection range from 6 to 10 years and from 55 to 75%, respectively. Pancreatic resection is effective for local control. However, extrapancreatic progression frequently occurs. With the introduction of novel systemic therapy options such as tyrosine kinase inhibitors, the prognosis of metastatic renal cell carcinoma has improved, and this will affect the role of pancreatic resection for metastases. Practical Implications: Pancreatic resection for isolated renal cell carcinoma is safe and effective, may confer a survival benefit and should, therefore, be considered in patients for whom no contraindication for surgery exists.
Gesehen am 24.06.2020